Characteristics and outcomes of cardiac arrest survivors with acute pulmonary embolism. (October 2020) - Dutta, Abhishek; Tayal, Bhupendar; Kragholm, Kristian Hay; Masmoudi, Youssef; Azizian, John; Mcdonald, Lawson; Goyal, Amandeep; Sogaard, Peter; Qureshi, Waqas T.
Abstract: Introduction: The characteristics and outcomes of patients that suffer cardiac arrest due to acute pulmonary embolism (PE) are not well studied. We compared the characteristics and outcomes of cardiac arrest survivors that suffered PE with other forms of cardiac arrest. Methods: Consecutive cardiac arrest survivors were enrolled that were able to survive for 24 h post cardiopulmonary resuscitation. Diagnosis of PE was confirmed by CT angiogram or high-probability of PE on ventilation perfusion scan after the successful resuscitation from cardiac arrest. Survival curves were examined and predictors of mortality in PE patients were examined in an adjusted Cox proportional hazard model. Results: Among the 996 cardiac arrest patients (mean age 62.6 ± 14.8 years, females 39.4%), 87 (8.7%) patients were found to have acute PE. The mortality rate of cardiac arrest survivors with and without acute PE was not significant different (68.3% vs. 64%). There were no significant differences in mortality among PE patients that received thrombolytics versus those who did not. Out of 87 patients, 33 (37.9%) required transfusion and had a bleeding complication. The risk of mortality in PE patients was predicted by older age, female sex, history of diabetes mellitus, end-stage renal disease and use of targeted temperature management. Conclusion: Cardiac arrest survivors with PE did not have significantly better survival than patients with non-PE related cardiac arrest. In addition, use of thrombolytics did not improve survival but these patients ended up requiring transfusion that could have off set the benefit of thrombolytics.